Digital transformation of construction companies based on BIM - Chupryna, Kh. (Ways to Improve Construction Efficiency, 2018)
Based on world experience, the prerequisites and the need for introducing the concept of digital transformation of construction organizations are identified and justified. The characteristic is given to the main obstacles to the digital transformation of construction organizations: transformational, innovative and managerial. The main stages of the formation of a successful digital strategy of a construction organization are formed. To develop a unified vision of the digital transformation of the organization, a radical restructuring of the processes is proposed in order to maximize the benefits of digitalization of activities, staff training and the recruitment of new employees taking into account the requirements for their digital literacy.